VALIDASI METODE ANALISIS KUERSETIN DARI EKSTRAK ETANOL DAUN KEMANGI (Ocimum sanctum L) SECARA SPEKTROFOTOMETRI UV-Vis - Evi Kurniawati; Tri Puji Lestari; Krisna Kharisma Pertiwi (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2024)
Basil leaves, scientifically known as Ocimum sanctum L., are a medicinal plant commonly used by the public because of their abundant secondary metabolite chemical compounds. One of them is flavonoids, secondary metabolites found in basil leaves, which have antioxidant properties. Quercetin, a flavonoid compound, exhibits valuable biological properties beyond its antioxidant effects, including antibacterial, anticancer, antiviral and anti-inflammatory activities. This research was carried out with the aim of determining the quercetin content contained in the ethanol extract of basil leaves (Ocimum sanctum L) by validated UV-Vis Spectrophotometry. Basil leaves are macerated with 70% ethanol. The extract is then concentrated using a rotary evaporator. Next, phytochemical screening was carried out to identify secondary metabolites in the extract, followed by UV-Vis spectrophotometric quantification. Based on the test results, it can be seen that the analysis of quercetin levels using UV-Vis spectrophotometry is validated for all parameters that meet the requirements. A significant relationship is shown by the linearity test, the correlation coefficient (r) is 0.9963. These results show good specificity, with test accuracy ranging from 90% to 107%, namely 103.9%. In addition, the precision test shows the %RSD value is less than 2%. The ethanol extract of basil leaves has an average quercetin content of 10.811% w/w.